First-line treatment disruption among post-menopausal women with HR+/HER2– metastatic breast cancer: a retrospective US claims study. (2nd December 2017) - Tang, Derek H.; Li, Nanxin; Du, Ella X.; Peeples, Miranda; Chu, Lihao; Xie, Jipan; Barghout, Victoria
Abstract: Objective: This study assessed disruption of first-line treatments initiated after the approval of the first CDK 4/6 inhibitor, palbociclib, among post-menopausal women with HR+/HER2– metastatic breast cancer (mBC) in the US. Methods: Post-menopausal women with HR+/HER2– mBC who initiated first-line endocrine therapy or chemotherapy (index therapy) between February 3, 2015 (palbociclib approval date) and February 29, 2016 (end of data) were identified from the Symphony Source Lx database. Patients were required to have continuous quarterly activity (defined as ≥1 pharmacy or medical claim) for 12 months prior to and 1 month after the initiation of the index therapy (index date). Treatment disruption was defined as a treatment gap of ≥60 days or adding an agent after the original therapy. Kaplan-Meier analyses were conducted to estimate treatment disruption rates during the 6 months following the index date. Patients without treatment disruption were censored at the end of continuous quarterly activity or end of data. Results: A total of 8, 160 and 2, 153 eligible patients initiated endocrine therapy or chemotherapy as their first-line mBC treatment, with a median follow-up of 6.7 and 7.6 months, respectively. The three most prevalent metastatic sites were bone (28.1–42.2%), liver (8.8–17.3%), and lung (8.6–9.5%). Overall, 37.7% ( n  = 3, 074) of patients receiving endocrine therapy and 86.1% ( n  = 1, 852) of patients receiving chemotherapy encountered treatment disruption at 6 months (log-rank test p  < .05). Conclusions: Treatment disruption rates of first-line therapies were sub-optimal among post-menopausal women with HR+/HER2– mBC, primarily driven by chemotherapy users. New therapies or interventions are needed to reduce treatment disruption in this patient population.